2014
DOI: 10.1371/journal.pone.0107165
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-Targeted TRAIL and a Smac Mimetic Synergize to Overcome Apoptosis Resistance in KRAS Mutant Colorectal Cancer Cells

Abstract: TRAIL is a death receptor ligand that induces cell death preferentially in tumor cells. Recombinant soluble TRAIL, however, performs poorly as an anti-cancer therapeutic because oligomerization is required for potent biological activity. We previously generated a diabody format of tumor-targeted TRAIL termed DbαEGFR-scTRAIL, comprising single-stranded TRAIL molecules (scTRAIL) and the variable domains of a humanized variant of the EGFR blocking antibody Cetuximab. Here we define the bioactivity of DbαEGFR-scTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
(66 reference statements)
1
29
0
Order By: Relevance
“…In addition, the expression levels of EGFR, HER2 and HER3 were determined in primary tumors of colorectal cancer cells, and corresponded with lymph node metastases and liver metastases (42,43). The dysregulation of human EGFR pathways by the overexpression or constitutive activation promote s tumor processes, angiogenesis and metastasis in several types of human cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Previous studies have demonstrated that tetrandrine inhibits cell metastasis in 4T1 breast cancer cells (18) and CT26 colorectal cancer cells in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the expression levels of EGFR, HER2 and HER3 were determined in primary tumors of colorectal cancer cells, and corresponded with lymph node metastases and liver metastases (42,43). The dysregulation of human EGFR pathways by the overexpression or constitutive activation promote s tumor processes, angiogenesis and metastasis in several types of human cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Previous studies have demonstrated that tetrandrine inhibits cell metastasis in 4T1 breast cancer cells (18) and CT26 colorectal cancer cells in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
“…The HT29 cells (1x10 5 ) were seeded into a 12-well plate and were exposed to EGF (100 ng/ml) and various concentrations of tetrandrine (0, 0.5, 1 or 2 µM) for 48 h at 37˚C. The conditioned media were collected, and the samples were separated by electrophoresis on an 8% SDS-polyacrylamide gel with 0.1% gelatin (Sigma-Aldrich).…”
Section: Cell Invasion Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In a first step, signals are normalized to a loading control, in order to minimize artifacts that are due to different loading amounts. Second, since raw signals depend on the specialties of the antibodies, the particular membranes and chemicals in use, they are usually additionally normalized to a reference condition (for examples see [2,3]). This second normalization is required for a comparison of data from different replicates.…”
Section: Introductionmentioning
confidence: 99%